Economic Tools for Merger Appraisal: A Theoretical and Empirical Standpoint - Fotis, Panagiotis N. (Journal of Reviews on Global Economics, 2014)
This paper presents in a retrospective manner economic tools for merger control and market delineation. Particularly, it focuses, via theoretical and empirical standpoint, on price based techniques for merger control such as tools of market delineation in one sided markets as the «Could Approach» of Critical Loss analysis, and tools for measuring the unilateral effects of a merger such as the Upward Pricing Pressure by Farrell & Shapiro (2010), the Gross Upward Price Pressure Index (2010) by Moresi (2010) and the Buying Power Index by Blair & Harrison (2010). The theoretical standpoint reveals that economic tools for merger control have been enhanced through the time in order to deal with the increasingly amount of merger cases, while the empirical standpoint supports the idea that competition economics have become a standard reference during the analysis of them. Even though competition analysis for antitrust and abuse of dominant position cases is considered to be a castle for lawyers, economists play a crucial role in quantifying the effects of mergers on competition.